Allergic : how our immune system reacts to a changing world - MacPhail, Theresa (Allen Lane, 2023)
An eye-opening investigation - combining reporting, history and cutting-edge science - into allergies and their rise in recent decadesHay fever. Peanut allergies. Eczema. Billions of people worldwide have some form of allergy; millions have one severe enough to seriously endanger their health. And over the past decade, the number of people diagnosed with allergy has been steadily increasing, an ever-growing medical burden on individuals, families, and our health care system. Medical anthropologist Theresa MacPhail, herself an allergy sufferer whose father died of a bee sting, set out to understand why. The result is a holistic and deeply researched examination of allergies, from their first medical description in 1819 to the mind-bending new treatments that are giving patients hope. MacPhail spent years interviewing hundreds of experts, patients and activists, in an effort to understand how recent changes in our environment and lifestyle are contributing to the dramatic rise in cases globally. Pollution, chemicals, antibiotics and, increasingly, climate change are all making our immune systems become more and more irritated. But, as she shows us in Allergic, understanding what is irritating us and why will help us to craft better environments in the future-so we can all breathe easier.